Language, Time, and Death. An Ethico-Philosophical Perspective Following Hegel, Heidegger, Lévinas, and Blanchot - Kaushal, Sanjay (ETHICS IN PROGRESS, 2022)
Our daily existence is affected by how we perceive death, be it our own’s death tocome or others’ death. The intimidating nature of death has the potential to affect our daily ethical existence in relation to the other, as is seen in various crises in human history. In such a context, since expansive literature in various approaches such as biological, sociological, psychological, and political addressing the question of death is already available, this essay presents an ethico-philosophical perspective on death and argues if death should be seen as the worst event that is to be experienced by being. In this essay, I correlate language, time, and death, contrasting popular analogies, i.e., death is possibility of impossibility (Hegel and Heidegger), and death is impossibility of possibility (Lévinas and Blanchot). Firstly, the essay stages the discussion with contrasting synchronic and diachronic perspectives of language, i.e., historical understanding of language and time in Hegelian terms and the messianic time in Lévinasian terms, to see how sensibility, i.e., universal meaning, is expressed through concept. Secondly, the essay sees how sensibility is expressed through a concept beyond dialectic opposition and negativity while acknowledging that the question of ethics arises only after the end of philosophy, for something is always inexpressible through expression; there is always remnant beyond philosophical significance. This essay not only argues language, time, and death as the ethical responsibility of the self towards the other, but also contributes to the understanding of language as ethics beyond philosophy, and death as passivity beyond ontology following Lévinas’s idea of messianic time and Blanchot’s views on literature and death.